Kajian Antibakteri Temulawak, Jahe dan Bawang Putih terhadap Salmonella typhimurium serta Pengaruh Bawang Putih terhadap Performans dan Respon Imun Ayam Pedaging - K G Wiryawan; S Suharti; M Bintang (Media Peternakan, 2005)
This research was conducted to investigate the antibacterial activity of powder of temulawak, ginger and garlic to S.typhimurium using modified agar well method. Preliminary study showed that garlic powder had the best antibacterial activity, therefore it was further tested in a feeding trial to evaluate the effect on growth performance and immune response in broiler chicken challenged with S. typhimurium (ST). Experimental treatments were arranged in Completely Randomized Design with four treatment and three replications (Negative control, positive control, garlic powder and tetracycline). Seventy-two Day-Old-Chickens with body weight 46,7 g strain Ã¢â‚¬Å“Hubbard WonokoyoÃ¢â‚¬Â were used in a 28 days experiment. Broiler chickens were fed garlic powder and tetracycline diets for 10 days and then challenged orally with ST 4,1 x 1011 cfu. Body weight, feed intake and salmonella colony in faeces were monitored. Blood serum was collected at 18-d after infection. Results indicated that there was no significant effect of garlic powder on body weight and feed intake, but feed intake tended to decrease. However, feed conversion ratio of ration with garlic powder was better than rations with tetracycline and other treatments. Salmonella population in faeces also decreased with addition of garlic powder in diets. Total protein serum was influenced by disease challenged. Serum immunoglobulin (gamma globulin) was not influenced by disease challenged, but addition garlic powder in diet tended to increase gamma-globulin concentration. It can be concluded that garlic powder has antibacterial activity to S.typhimurium. Furthermore, this result indicated that some beneficial effect of dietary garlic powder at 2,5% supplementation on growth performance and no effect on immune response in the presence of ST-challenge. Key words : antibacterial, temulawak, ginger, garlic, Salmonella, chicken